2011
DOI: 10.1161/atvbaha.111.222745
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Induces Antiinflammatory Phenotype in Macrophages

Abstract: Objectives Apolipoprotein E (apoE) exerts potent anti-inflammatory effects. We here investigated the effect of apoE on the functional phenotype of macrophages. Methods and Results Human apoE receptors VLDL-R or apoER2 were stably expressed in RAW264.7 mouse macrophages. In these cells apoE downregulated markers of the pro-inflammatory M1 phenotype (iNOS, IL-12, MIP-1α), but upregulated markers of the anti-inflammatory M2 phenotype (arginase-I, SOCS3, IL-1RA). In addition, M1 macrophage responses (migration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
213
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(225 citation statements)
references
References 36 publications
(39 reference statements)
10
213
1
1
Order By: Relevance
“…Overexpression of VLDLR increased ␤-VLDL-induced lipid accumulation (30). In contrast, it has been shown that treatment of VLDLR-and apoER2-overexpressing macrophages with apoE down-regulated proinflammatory gene and up-regulated anti-inflammatory gene expression in these macrophages (31). Furthermore, a VLDLR deficiency increased intimal thickening after vascular injury and increased necrosis in atherosclerotic lesions (32).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of VLDLR increased ␤-VLDL-induced lipid accumulation (30). In contrast, it has been shown that treatment of VLDLR-and apoER2-overexpressing macrophages with apoE down-regulated proinflammatory gene and up-regulated anti-inflammatory gene expression in these macrophages (31). Furthermore, a VLDLR deficiency increased intimal thickening after vascular injury and increased necrosis in atherosclerotic lesions (32).…”
Section: Discussionmentioning
confidence: 99%
“…This effect can be also mediated by hepatic ApoE, as was proven in mice lacking macrophage-derived ApoE, and is responsible for anti-aterogenic action even without lowering plasma cholesterol levels [9][10][11] . The protein also induce the synthesis of NO in vessel wall 12 and has numerous anti-inflammatory effects 13,14 ApoE is polymorphic, with three isoforms common in general population: E2, E3 and E4. The three isoforms differ in two amino-acids at residues 112 and 158 of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that ApoE shifts the balance from a pro-inflammatory to an anti-inflammatory cytokine profile [50].…”
Section: Role Of Apolipoprotein E and Ldls In Macrophage Polarizationmentioning
confidence: 91%